Pregunta
upstudy study bank question image url

Fill in the blanks under each radical to make the statement true. \( (3-\sqrt{\square})(3+\sqrt{ })=4 \)

Ask by Little John. in Kenya
Feb 09,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Fill in the blanks with 5: \[ (3-\sqrt{5})(3+\sqrt{5})=4 \]

Solución

To solve the equation \( (3-\sqrt{a})(3+\sqrt{b})=4 \), we can use the difference of squares formula, which states that \( (x-y)(x+y) = x^2 - y^2 \). Here, we can identify: - \( x = 3 \) - \( y = \sqrt{b} \) Thus, we can rewrite the expression as: \[ (3-\sqrt{a})(3+\sqrt{b}) = 3^2 - (\sqrt{b})^2 = 9 - b \] Setting this equal to 4 gives us: \[ 9 - b = 4 \] Now, we can solve for \( b \): \[ b = 9 - 4 = 5 \] Next, we can also express the equation in terms of \( a \): \[ (3-\sqrt{a})(3+\sqrt{b}) = 4 \] Substituting \( b = 5 \): \[ (3-\sqrt{a})(3+\sqrt{5}) = 4 \] Now, we can expand this: \[ 3(3+\sqrt{5}) - \sqrt{a}(3+\sqrt{5}) = 4 \] Calculating \( 3(3+\sqrt{5}) \): \[ 9 + 3\sqrt{5} - \sqrt{a}(3+\sqrt{5}) = 4 \] Rearranging gives: \[ 9 + 3\sqrt{5} - 4 = \sqrt{a}(3+\sqrt{5}) \] \[ 5 + 3\sqrt{5} = \sqrt{a}(3+\sqrt{5}) \] To isolate \( \sqrt{a} \), we can divide both sides by \( 3+\sqrt{5} \): \[ \sqrt{a} = \frac{5 + 3\sqrt{5}}{3+\sqrt{5}} \] Now, we can rationalize the denominator: \[ \sqrt{a} = \frac{(5 + 3\sqrt{5})(3-\sqrt{5})}{(3+\sqrt{5})(3-\sqrt{5})} \] Calculating the denominator: \[ (3+\sqrt{5})(3-\sqrt{5}) = 9 - 5 = 4 \] Calculating the numerator: \[ (5 + 3\sqrt{5})(3-\sqrt{5}) = 15 - 5\sqrt{5} + 9\sqrt{5} - 15 = 4\sqrt{5} \] Thus: \[ \sqrt{a} = \frac{4\sqrt{5}}{4} = \sqrt{5} \] Squaring both sides gives: \[ a = 5 \] In conclusion, the values to fill in the blanks are: - \( a = 5 \) - \( b = 5 \) So the completed statement is: \[ (3-\sqrt{5})(3+\sqrt{5})=4 \]

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

In the expression \( (3-\sqrt{\square})(3+\sqrt{ })=4 \), we can utilize the difference of squares formula, which states that \( (a-b)(a+b) = a^2 - b^2 \). Thus, we can set it up as follows: 1. Here, \( a = 3 \) and \( b = \sqrt{\square} \) and \( \sqrt{ } \). Since \( b \) appears in both radical parts, we can denote it as \( b = \sqrt{x} \) for simplicity. Now, we rewrite the equation using this formula: \[ 3^2 - (\sqrt{x})^2 = 4 \] This simplifies to: \[ 9 - x = 4 \] 2. Rearranging gives us: \[ x = 9 - 4 = 5 \] 3. Hence, we fill in the blanks: - For the first blank \( \square \), fill in \( 5 \) - For the second blank, since it's the same expression as the first, it will also be \( 5 \) So the completed statement is: \( (3-\sqrt{5})(3+\sqrt{5})=4 \).

preguntas relacionadas

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad